Cole - Gill, Brendan 1914-1997 (Overlook Press, 2000)
"The lyrics of nearly two hundred songs - among them such favorites as "Love for Sale," "I Love Paris," "I Get a Kick Out of You," "In the Still of the Night," and "Begin the Beguine" - are featured alongside music sheets, private letters, examples of works in progress in Cole's own hand, and hundreds of pictures from the private albums of Linda and Cole Porter. It adds up to a marvelous party capturing Cole's irrepressible spirit. Glimpses of Cole and his friends dazzling each other and the world at the Palazzo Rezzonico or on the beach at Antibes, of productions of Silk Stockings, Broadway Melody of 1940, Can-Can, Kiss Me, Kate, Panama Hattie, Something for the Boys, Anything Goes, High Society, and Red, Hot, and Blue are just part of the scene... along with another look at Monty, Noel, Elsa, Tallulah, Gerald, and Sara, and of Ethel Merman, Bert Lahr, Bea Lillie, Fred Astaire, Gertrude Lawrence, Victor Moore, Rita Hayworth, and Danny Kaye... all return us to the decadent days." "A graceful and revealing biographical essay by the late and incomparable Brendan Gill sets the tone for a book as stylish, as saucy, as self-confident, and as beguiling as the era it recreates."--BOOK JACKET.